2023
DOI: 10.1109/tvcg.2023.3247110
|View full text |Cite
|
Sign up to set email alerts
|

CardioGenesis4D: Interactive Morphological Transitions of Embryonic Heart Development in a Virtual Learning Environment

Abstract: Fig. 1: A collage of multiple stages of the transformation of the heart tube during embryological cardiogenesis as seen in the VRLE. The center heart shows the transformation in progress: the tracked hands of the user follow the arrows indicating growth directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Specifically, this study claims that implementing and using ICTs, such as a virtual learning environment (VLE), depends on franchise’s acceptance and e-learning systems’ elements. However, although research has analyzed the concept of VLE in different contexts, such as education (Chanmi Hwang and Song, 2023; Rieger and Risch, 2023) and health (Schott et al , 2023), empirical insights on franchising systems are almost completely absent. Although abundant research has been developed on the use of ICTs in franchising, it is observed that the contribution and challenges of specific ICTs for knowledge sharing remain unclear (Pandey et al , 2021; Chen et al , 2013) and underrepresented in empirical studies (Nguyen and Burgess, 2014; Bernal et al , 2020) missing enough normative information to guide franchising systems to decide about the more appropriate ICT to facilitate knowledge sharing.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, this study claims that implementing and using ICTs, such as a virtual learning environment (VLE), depends on franchise’s acceptance and e-learning systems’ elements. However, although research has analyzed the concept of VLE in different contexts, such as education (Chanmi Hwang and Song, 2023; Rieger and Risch, 2023) and health (Schott et al , 2023), empirical insights on franchising systems are almost completely absent. Although abundant research has been developed on the use of ICTs in franchising, it is observed that the contribution and challenges of specific ICTs for knowledge sharing remain unclear (Pandey et al , 2021; Chen et al , 2013) and underrepresented in empirical studies (Nguyen and Burgess, 2014; Bernal et al , 2020) missing enough normative information to guide franchising systems to decide about the more appropriate ICT to facilitate knowledge sharing.…”
Section: Introductionmentioning
confidence: 99%